Mechanistic approach and therapeutic strategies in menstrual and non-menstrual migraine - Tanya Mani; Munira Murtaza; Rukaiah Fatma Begum; H. Gayathri; M. Sumithra (Future Science OA)
Migraine is a common condition that can cause intense headaches, often on one side of the head, along with symptoms like nausea and sensitivity to light and sound. These headaches can be triggered by various factors, including stress, changes in hormones, sleep disturbances, diet, and even gut health. Migraines are more frequent in women, particularly those under 45, and this may be linked to hormones. After age 45, this difference between men and women becomes less noticeable. Women tend to experience migraines that are more severe and last longer than men, with menstrual migraines affecting about 22% of women during nearly half of their menstrual cycles, and 7.6% of women with migraines. Treatments for migraines include medications, lifestyle changes, and alternative therapies, all of which aim to address the different ways migraines can affect people. This review explores these aspects in detail.